2012
DOI: 10.1017/s0007114512003340
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity in ad libitum-fed mice: food texture overrides the effect of macronutrient composition

Abstract: Diet-induced obesity in mice can be achieved through the use of diets with different macronutrient compositions and textures. We aimed at determining the contribution of macronutrient composition to obesity development and associated pathophysiological changes in mice. C57BL/6N mice were offered a control, a high-fat or a Western-style diet, either as pellet (H for hard) or with identical composition in powder form (S for soft), resulting in C-S, C-H, HF-H, HF-S, W-H and W-S groups, respectively. Body fat dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
(51 reference statements)
1
27
2
Order By: Relevance
“…Mean Lactobacillus relative abundances were generally higher in the HF group (12.5 vs 9.7%), but diet-associated differences were not statistically significant due to marked interindividual variations. It is worth mentioning that, when compared with studies showing rapid changes in bacterial communities due to high-calorie diets, the data obtained in the present work relate to adaptation of the gut ecosystem and the host to longterm feeding (12 weeks) (Desmarchelier et al, 2012(Desmarchelier et al, , 2013, which may explain, together with differences in HF diet composition, some of the variations High-fat diet alters gut microbiota physiology H Daniel et al observed as well as differences with data from the literature (for example, regarding abundance changes of Bacteroides or Erysipelotrichaceae).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Mean Lactobacillus relative abundances were generally higher in the HF group (12.5 vs 9.7%), but diet-associated differences were not statistically significant due to marked interindividual variations. It is worth mentioning that, when compared with studies showing rapid changes in bacterial communities due to high-calorie diets, the data obtained in the present work relate to adaptation of the gut ecosystem and the host to longterm feeding (12 weeks) (Desmarchelier et al, 2012(Desmarchelier et al, , 2013, which may explain, together with differences in HF diet composition, some of the variations High-fat diet alters gut microbiota physiology H Daniel et al observed as well as differences with data from the literature (for example, regarding abundance changes of Bacteroides or Erysipelotrichaceae).…”
Section: Discussionmentioning
confidence: 73%
“…209.1/211-2531-41/03). The design of mouse trials has been described elsewhere (Desmarchelier et al, 2012(Desmarchelier et al, , 2013. Details are given in the Supplementary Methods.…”
Section: Animals and Samplesmentioning
confidence: 99%
“…The results of that study indicated that regardless of diet composition, all mice fed powdered diets had similar weight gains [24]. This suggests that the texture and hardness of the food, rather than the nutrient composition, promoted hyperphagia and obesity [24].…”
Section: Concentration (Nm)mentioning
confidence: 96%
“…Mice fed pelleted diets in the current study were significantly lighter than mice fed powdered diets in the previous study as early as 8 weeks of age (p < 0.001) and continuing until animals were sacrificed at 18 weeks of age ( Figure 6) (p < 0.001). The associations between diet format and obesity have been examined extensively in rodent models [22] [23] [24]. Ford et al described the association between food consumption and diet hardness in mice, and observed that increasing the hardness of food, negatively impacted growth and food intake [25].…”
Section: Concentration (Nm)mentioning
confidence: 99%
See 1 more Smart Citation